Evaluation of the Impact of the 2012 Rhode Island Health Care Worker Influenza Vaccination Regulations: Implementation Process and Vaccination Coverage - Kim, Hanna (J Public Health Manag Pract, 2015)
CONTEXT: In October 2012, the Rhode Island Department of Health (HEALTH) amended its health care worker (HCW) vaccination regulations to require all HCWs to receive annual influenza vaccination or wear a surgical mask during direct patient contact when influenza is widespread. Unvaccinated HCWs failing to wear a mask are subject to a fine and disciplinary action. OBJECTIVE: To describe the implementation of the 2012 Rhode Island HCW influenza vaccination regulations and examine their impact on vaccination coverage. DESIGN: Two data sources were used: (1) a survey of all health care facilities subject to the HCW regulations and (2) HCW influenza vaccination coverage data reported to HEALTH by health care facilities. Descriptive statistics and paired t tests were performed using SAS Release 9.2. SETTING AND PARTICIPANTS: For the 2012-2013 influenza season, 271 inpatient and outpatient health care facilities in Rhode Island were subject to the HCW regulations. MAIN OUTCOME MEASURE: Increase in HCW influenza vaccination coverage. RESULTS: Of the 271 facilities, 117 facilities completed the survey (43.2%) and 160 facilities reported vaccination data to HEALTH (59.0%). Between the 2011-2012 and 2012-2013 influenza seasons, the proportion of facilities having a masking policy, as required by the revised regulations, increased from 9.4% to 94.0% (P< .001). However, the proportion of facilities implementing Advisory Committee on Immunization Practices–recommended strategies to promote HCW influenza vaccination did not increase. The majority of facilities perceived benefits to collecting HCW influenza vaccination data, including strengthening infection prevention efforts (83.2%) and improving patient and coworker safety (75.2%). Concurrent with the new regulations, influenza vaccination coverage among employee HCWs in Rhode Island increased from 69.7% in the 2011-2012 influenza season to 87.2% in the 2012-2013 season. CONCLUSION: Rhode Island's experience demonstrates that statewide HCW influenza vaccination requirements incorporating mask wearing and moderate penalties for noncompliance can be effective in improving influenza vaccination coverage among HCWs.